Role of long non-coding RNAs in metabolic reprogramming of gastrointestinal cancer cells - Kang Wang; Yan Lu; Haibin Li; Jun Zhang; Yongle Ju; Manzhao Ouyang (Cancer Cell International, 2024)
Abstract Metabolic reprogramming, which is recognized as a hallmark of cancer, refers to the phenomenon by which cancer cells change their metabolism to support their increased biosynthetic demands. Tumor cells undergo substantial alterations in metabolic pathways, such as glycolysis, oxidative phosphorylation, pentose phosphate pathway, tricarboxylic acid cycle, fatty acid metabolism, and amino acid metabolism. Latest studies have revealed that long non-coding RNAs (lncRNAs), a group of non-coding RNAs over 200 nucleotides long, mediate metabolic reprogramming in tumor cells by regulating the transcription, translation and post-translational modification of metabolic-related signaling pathways and metabolism-related enzymes through transcriptional, translational, and post-translational modifications of genes. In addition, lncRNAs are closely related to the tumor microenvironment, and they directly or indirectly affect the proliferation and migration of tumor cells, drug resistance and other processes. Here, we review the mechanisms of lncRNA-mediated regulation of glucose, lipid, amino acid metabolism and tumor immunity in gastrointestinal tumors, aiming to provide more information on effective therapeutic targets and drug molecules for gastrointestinal tumors. Graphical Abstract